Who Pays for Financial Crises? : Price and Quantity Rationing of Different Borrowers by Domestic and Foreign Banks - Berger, Allen; Makaew, Tanakorn; Turk-Ariss, Rima. (Washington, D.C. : International Monetary Fund, 2018)
Financial crises result in price and quantity rationing of otherwise creditworthy business borrowers, but little is known about the relative severity of these two types of rationing, which borrowers are rationed most, and the roles of foreign and domestic banks. Using a dataset from 50 countries containing over 18,000 business loans with information on the lender, the borrower, and contract terms, we find that publicly-listed borrowers are rationed more by prices or interest rates, whereas privately-held borrowers are rationed more by the number of loans. Also, the global financial crisis appears to have changed how banks price borrower risk. Further, there are important differences between foreign and domestic banks and between U.S. and non-U.S. loans.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet